KONFLIK SOSIAL DALAM NOVEL JARING KALAMANGGA KARYA SUPARTO BRATA DAN RELEVANSINYA SEBAGAI MATERI AJAR APRESIASI SASTRA JAWA DI SEKOLAH MENENGAH ATAS - Nungki Adelina Damayanti; Raheni Suhita; Nugraheni Eko Wardani (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2019)
The objectives of research were to describe the social conflict existing in novel Jaring Kalamangga by Suparto Brata and to describe its relevance to be the teaching material of Javanese Letters Appreciation in Senior High Schools.The method used in this research is descriptive qualitative method. Data obtained by using content analysis and interviews with informants. The validity of the data obtained by triangulation and triangulation theory. Sources of data in this study are documents and informants. The sampling technique used in this research is purposive sampling. Research procedure includes the preparation phase, the implementation phase and a final stage.The results of the analysis of novel Jaring Kalamangga relating to social conflict shows that; 1) there are four causes of social conflict in the novel Jaring Kalamangga soeparto work Brata. namely crime, family disorganization, problems young people in modern society and violations of the norms of society and 2) novel Jaring Kalamangga soeparto work Brata eligible as an alternative teaching materials Javanese literature appreciation because there is the relevance of social conflicts in it.